2016
DOI: 10.1515/frp-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Communities of fungi in decomposed wood of oak and pine

Abstract: The abundance and diversity of wood decomposing fungi were investigated by isolating and cultivating filamentous fungi from wood and by detection of fruit bodies of ascomycetous and basidiomycetous fungi. The objective was to study the impact of forest management on fungi in 100-year-old oak and 87-year-old Scots pine forests in Northern Poland. Fungi were found on coarse woody debris of decayed stumps and fallen logs, boughs and branches in each of the three (managed and unmanaged) examined stands. In total, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 23 publications
(28 reference statements)
7
20
0
Order By: Relevance
“…Armillaria gallica and A. cepistipes were most abundant in wood in the 2 nd decay class, consistent with earlier findings (Kwaśna et al, 2016b). Both species are known as opportunistic parasites in weakened or stressed trees (particularly A. gallica in oak).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Armillaria gallica and A. cepistipes were most abundant in wood in the 2 nd decay class, consistent with earlier findings (Kwaśna et al, 2016b). Both species are known as opportunistic parasites in weakened or stressed trees (particularly A. gallica in oak).…”
Section: Discussionsupporting
confidence: 91%
“…In the six 3-30-year-old Q. petraea logs there were 264 307 different OTUs, which is 127-fold more than the 2 080 OTUs found in nine samples of 3-year-old Q. rubra logs using high-throughput sequencing (by van der Wal et al, 2017), but less than the 687 662 and 1 861 279 OTUs found in 20 samples of broadleaved trees from two locations in neotropical Atlantic forests using massively parallel sequencing (Vaz et al, 2017). There were also 277 fungal taxa, which is more than the 141 taxa detected in deadwood of Quercus robur L. using the classical method based on isolation and microscopic analysis (Kwaśna et al, 2016b), the 100 taxa detected in neotropical Atlantic forests (Vaz et al, 2017), and the 15 species detected in Q. rubra logs (by van der Wal et al, 2017). In two other tree species, beech and Scots pine, respectively 96 and 138 fungal taxa were detected by isolation and microscopic analysis (Fukasawa et al, 2009;Kwaśna et al, 2016b).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In our research, the amount of woody debris and the fungal richness (12 species) were lower in the managed stand than in the reserve (28 species), but higher than in other managed state forests. Kwaśna et al (2016) described 21 Basidiomycota species colonizing 100-year-old Scots pine CWD in the Torzym Forest District.…”
Section: Discussionmentioning
confidence: 99%